2015
DOI: 10.1371/journal.pone.0144089
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Climate Change for Bird Conservation in the Southwestern U.S. under Three Alternative Futures

Abstract: Future expected changes in climate and human activity threaten many riparian habitats, particularly in the southwestern U.S. Using Maximum Entropy (MaxEnt3.3.3) modeling, we characterized habitat relationships and generated spatial predictions of habitat suitability for the Lucy’s warbler (Oreothlypis luciae), the Southwestern willow flycatcher (Empidonax traillii extimus) and the Western yellow-billed cuckoo (Coccyzus americanus). Our goal was to provide site- and species-specific information that can be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 53 publications
0
18
0
2
Order By: Relevance
“…In contrast, land‐use models outperformed climate models for 18 farmland bird species in the United Kingdom (Eglington & Pearce‐Higgins, ). Similarly, vegetation‐based species distribution models had superior performance than climate‐based models for 79 Spanish bird species (Seoane et al, ) and for three bird species in New Mexico (Friggens & Finch, ). Two studies focused on colonization and extinction rates found mixed results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, land‐use models outperformed climate models for 18 farmland bird species in the United Kingdom (Eglington & Pearce‐Higgins, ). Similarly, vegetation‐based species distribution models had superior performance than climate‐based models for 79 Spanish bird species (Seoane et al, ) and for three bird species in New Mexico (Friggens & Finch, ). Two studies focused on colonization and extinction rates found mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…during the breeding season drive changes in bird distributions because inappropriate habitat will not provide sufficient food and shelter for breeding birds (Friggens & Finch, 2015;Iglecia, Collazo, & McKerrow, 2012). For the Eastern Wood Pewee, we defined appropriate habitats as deciduous forest, evergreen forest, and mixed forest (Hamel, 1992).…”
Section: Changes In the Amount Of Appropriate Habitat Locally Availablementioning
confidence: 99%
“…Long-term perturbations facilitated by changes in land use, high demands placed on limited water resources, introduction of invasive species, and human-modification of the natural hydrological regime has made it harder to simultaneously fulfill the needs of humans and wildlife [ 5 , 15 ]. These environmental stressors have substantially changed both physiognomy and function of the MRGV and raised concern for the persistence of some fish and wildlife species [ 16 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coccyzus ferrugineus utiliza sitios costeros como áreas de forrajeo y anidación, probablemente porque tienen una elevada disponibilidad de presas a un costo energético bajo en comparación con áreas de mayor altitud, donde la vegetación es más densa y la búsqueda posiblemente más desgastante. Por estas mismas razones el ciclo reproductivo de C. americanus requiere hábitats húmedos (Russell & Holmes, 2015;Friggens & Finch, 2015).…”
Section: Discussionunclassified
“…Otras especies del género Coccyzus actualmente se encuentran amenazadas por invasión de especies alóctonas tanto vegetales como animales, así como por el cambio climático, que afecta negativamente a las presas de estas especies (Friggens & Finch, 2015). Por ello, estudios sobre la ecología de C. ferrugineus en base a los requerimientos de hábitat de la especie, así como de su densidad poblacional, son indispensables para categorizar las amenazas que le afectan y para poder ejercer un plan de manejo que incluya áreas de reproducción y programas de restauración ecológica (Woinarski et al, 2017).…”
Section: Discussionunclassified